Effect of adhesion layer on the optical scattering properties of plasmonic Au nanodisc - Kim, Jooyoung; Cho, Kyuman; Lee, Kyeong-Seok (KOREAN INST METALS MATERIALS, 2008)
Metallic nanostructures have great potential for bio-chemical sensor applications due to the excitation of localized surface plasmon and its sensitive response to environmental change. Unlike the commonly explored absorption-based sensing, the optical scattering provides single particle detection scheme. For the localized surface plasmon resonance spectroscopy, the metallic nanostructures with controlled shape and size have been usually fabricated on adhesion-layer pre-coated transparent glass substrates. In this study, we calculated the optical scattering properties of plasmonic Au nanodisc using a discrete dipole approximation method and analyzed the effect of adhesion layer on them. Our result also indicates that there is a trade-off between the surface plasmon damping and the capability of supporting nanostructures; in determining the optimal thickness of adhesion layer. Marginal thickness of Ti adhesion layer for supporting Au nanostructures fabricated on a silica glass substrate was experimentally analyzed by an adhesion strength test using a nano-indentation technique.
Keywords: DISCRETE-DIPOLE APPROXIMATION; METAL NANOPARTICLES; ASPECT RATIO; SHAPE; ABSORPTION; PARTICLES; NANORODS; SIZE